Reworked Oligo-Miocene Corals from North-eastern Libya: Implications for Paleoenvi-ronment and Paleogeographic Importance - Belkasim K. Khameiss; Ahmed M. Muftah; William H. Hoyt, Mohamed A. Masoud; Richard H. Fluegeman (Libyan Journal of Science &Technology, 2026)
The sedimentary successions of northeastern Libya preserve diverse coral assemblages that provide valuable insights into Oligocene–Miocene marine environments along the southern margin of the Tethys Ocean. The Middle to Upper Oligocene Al Abraq Formation of Wadi Derna, the meandroid coral Meandrina subcircularis, an ex-situ coral, occurs in non-reefal skeletal limestones deposited in a shoal–channel complex. Its highly sinuous, uniserial valleys and well-developed paliform lobes indicate morphological adaptations to fluctuating hydrodynamic regimes and episodic sediment influx. Elsewhere, a massive colony of the reef-building coral Porites solida was recovered ex-situ from Wadi El Zeitun near Tobruk, representing material reworked from the Middle Miocene Al Jaghboub Formation. The specimen, characterized by compact, radially septate corallites and a dome-shaped colony form, reflects deposition in high-energy, shallow marine reefal settings. Both occurrences exhibit evidence of storm-related reworking. highlighting the role of episodic high-energy events in the transport and redistribution of coral material across carbonate platforms. Together, these findings provide a framework for reconstructing Oligocene–Miocene palaeoecological conditions in Cyrenaica and emphasize the importance of coral taphonomy for interpreting depositional dynamics, tectonic influences, and the broader paleogeographic evolution of the southern Tethyan margin